2013
DOI: 10.3389/fnbeh.2013.00140
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis for the Ability of Atypical Antipsychotic Drugs to Improve Cognition in Schizophrenia

Abstract: Cognitive impairments are considered to largely affect functional outcome in patients with schizophrenia, other psychotic illnesses, or mood disorders. Specifically, there is much attention to the role of psychotropic compounds acting on serotonin (5-HT) receptors in ameliorating cognitive deficits of schizophrenia. It is noteworthy that atypical antipsychotic drugs (AAPDs), e.g., clozapine, melperone, risperidone, olanzapine, quetiapine, aripiprazole, perospirone, blonanserin, and lurasidone, have variable af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 42 publications
(61 reference statements)
0
33
0
1
Order By: Relevance
“…Further studies of the effects of 5-HT 1A receptor agonists and antagonists on social recognition are needed. Previously, Sumiyoshi et al (2001aSumiyoshi et al ( , 2001bSumiyoshi et al ( , 2007 reported that treatment with tandospirone (or buspirone), 5-HT 1A receptor agonists, improved cognition including executive function and verbal learning in patients with schizophrenia, indicating a key role of 5-HT 1A receptor in cognition in patients (Meltzer and Sumiyoshi, 2008;Sumiyoshi et al, 2013). Taken together, it seems that brexpiprazole can ameliorate cognitive deficits associated with NMDA receptor dysfunction, via its 5-HT 1A agonistic activity.…”
Section: Discussionmentioning
confidence: 93%
“…Further studies of the effects of 5-HT 1A receptor agonists and antagonists on social recognition are needed. Previously, Sumiyoshi et al (2001aSumiyoshi et al ( , 2001bSumiyoshi et al ( , 2007 reported that treatment with tandospirone (or buspirone), 5-HT 1A receptor agonists, improved cognition including executive function and verbal learning in patients with schizophrenia, indicating a key role of 5-HT 1A receptor in cognition in patients (Meltzer and Sumiyoshi, 2008;Sumiyoshi et al, 2013). Taken together, it seems that brexpiprazole can ameliorate cognitive deficits associated with NMDA receptor dysfunction, via its 5-HT 1A agonistic activity.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the add-on treatment with APZ might be interesting because this SGA combines partial 5HT 1A agonism with complex effects on GABAergic and glutamatergic neurotransmission [72,174,175]. Agonism at 5HT 1A [176,177] as well as antagonistic effects at 5HT 6 and 5HT 7 receptors, as seen with asenapine and lurasidone, may exert pro-cognitive effects [178]. A third mode of augmentation might be add-on treatment trials to enhance psychotherapy because pro-glutamatergic substances might stimulate learning processes.…”
Section: Suggestions For Forthcoming Clinical Trialsmentioning
confidence: 96%
“…Several studies of various classes of ligands with an arylpiperazine moiety in their structure have been reported and these efforts have led to successful drugs such as buspirone, perospirone, ziprasidone, and aripiprazole. [1][2][3][4] Generally, CNS agents with arylpiperazine-based template are characterized by three structural moieties (i.e. aryl group linked to the piperazine, alkyl chain with different length, heterocyclic terminal fragment), which can be modified to modulate specific properties such as pharmacokinetic, affinity, and selectivity for different targets (Fig.1).…”
Section: Bioorganic and Medicinal Chemistry Lettersmentioning
confidence: 99%